Про проблему визначення місця немайнових прав учасників господарських товариств в системі цивільних прав - Жорнокуй, В. Г.; Zhornokui, V. H.; Жорнокуй Валентина Григорівна (Право та інновації. – 2015. – № 4 (12). – С. 51–57, 2015)
У поданій науковій статті автором запропоноване власне бачення наукової проблеми щодо визначення місця немайнових прав учасників господарських товариств у системі цивільних прав. На підставі порівняльного аналізу категорій «майнове і немайнове» право та «немайнове і особисте» право робиться висновок про неможливість вивчення корпоративних прав як особистих, тобто тих, що можуть належати виключно фізичним особам. Результатом проведеного дослідження є висновок про те, що цивільне законодавство не дає підстав однозначно визначити місце немайнових прав учасників господарських товариств у системі цивільних прав.

Civil law regulates personal non-property and property relations based on legal equality, free will, property independence of their members. It may seem that the presented axiom enshrined in legislation, has been increasingly in the recent years criticized in the context of extending the object of legislative guaranteeing civil relations. Particularly acute there are discussions between the civil and legal, economic and legal schools in regard to the feasibility of inclusion of corporate relations into the object of regulation of civil law. Therefore, special attention is paid on a number of unresolved issues that are essential in clarifying the legal nature of corporate relations. One of such problematic aspects is their content. The urgency of choosing this problem is caused by different approaches both within the legislation and among scholars to ascertain the legal nature of the rights of business companies’ members in general and each right or power in particular.

В представленной научной статье автором предложено собственное видение научной проблемы относительно определения места неимущественных прав участников хозяйственных обществ в системе гражданских прав. На основании сравнительного анализа категорий «имущественное и неимущественное» право и «неимущественное и личное» право делается вывод о невозможности изучения корпоративных прав как личных, то есть тех, которые могут принадлежать исключительно физическим лицам. Результатом проведенного исследования является вывод о том, что гражданское законодательство не дает оснований однозначно определить место неимущественных прав участников хозяйственных обществ в системе гражданских прав.
On the problem of determining the place of non-property rights of the members of business companies in the system of civil rights
О проблеме определения места неимущественных прав участников хозяйственных обществ в системе гражданских прав
Keywords: Господарське право. Business Law. Хозяйственное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; корпоративні відносини; суб’єктивне корпоративне право; майнове право; немайнове право; особисте немайнове право; учасники господарських товариств; corporate relations; subjective corporate right; property right; non-property right; personal non-property right; members of business companies; корпоративные отношения; субъективное корпоративное право; имущественное право; неимущественное право; личное неимущественное право; участники хозяйственных обществ